HOME-BASED CARE AND LIFE QUALITY FOR ELDERLY COPD PATIENTS: A MIXED-METHODS EVALUATION IN A COASTAL HOSPITAL - Winda Sari Siregar; Ermi Girsang; Sri Lestari Ramadhani Nasution (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a significant global health challenge, particularly among the elderly population, who are at high risk of exacerbations and have limited mobility. Home care services have emerged as an innovative strategy to improve the accessibility and sustainability of care outside of hospital settings. This study aims to analyze the effectiveness of a home care program on the quality of life and medication adherence of elderly patients with COPD at RSAL Dr. Komang Makes Belawan. This study employed a mixed-methods design with a sequential explanatory approach. The quantitative phase involved 35 respondents selected via a total sampling approach. The instruments used included the VQ11 questionnaire to measure quality of life and the MMRC scale to assess dyspnea severity. The qualitative phase was conducted through in-depth interviews with patients, families, and healthcare providers to explore subjective experiences during the intervention. Data analysis integrated inferential statistical tests and thematic analysis to obtain a comprehensive understanding. Findings demonstrated significant clinical improvement, with patients’ dyspnea levels decreasing from an average MMRC Grade 3 to Grade 1 post-intervention. Quality of life scores (VQ11) improved from the moderate/severe category to the good/very good category. Additionally, the frequency of monthly exacerbations decreased drastically, from an average of 3 to 1. Qualitative data reinforced these findings by identifying three main themes: increased psychological safety, professionalism in healthcare services, and strengthening the family’s role in monitoring treatment adherence. The home-based care program proved effective in improving the quality of life and treatment adherence among elderly COPD patients. This success was driven by integrating routine clinical monitoring at home and empowering families as the primary support system. This study recommends home-based care as a standard model in the management of long-term chronic diseases to optimize patient health outcomes and healthcare system efficiency.